SRICTUROPLASTY IN TUBERCULOUS SMALL BOWEL STRICTURES - Akbar, Muhammad (Journal of Ayub Medical College Abbottabad, 2003)
Background: This study was conducted at DHQ Hospital Hangu, Babul Madina Medical Centre & Shifa Medical Centre Hangu from March 1995 to February 2001 to evaluate the presentation of tuberculous small bowel strictures and assess the usefulness and applicability of stricturoplasty to these lesions. Methods: Ten patients were included in the study in whom the diagnosis of tuberculous small bowel strictures was made on laparotomy and histopathological examination of the tissues taken from the strictures. Heinki/Mikulikz's type stricturoplasty was done in all the cases. The patients were kept on antitubercular drugs and were followed for assessment of outcome. Results: Seventy percent of the patients' presented/ operated upon in emergency. Age ranged from twenty to forty years with mean age 31.5 years. Male to female ratio was 6:4. Weight loss and malnutrition were the most common associated features. Terminal ileum alone was involved in 50% of the cases. The strictures were solitary in six and multiple in four cases. The lesions were acute in four and chronic in six patients. Stricturoplasty worked well both in acute and chronic cases. Conclusion: Stricturoplasty is safe, simple, and easy procedure particularly suitable at poorly equipped and under staffed district hospitals. Keywords: Intestinal tuberculosis, Strictures, stricturoplasty.